Training and conditioning young athletes. Science-based training to maximize strength, power, speed, agility, flexibility, and endurance - Bompa, T. O.; Sarandan, S. O. (Human Kinetics, 2023)
With more and more young athletes specializing in sport year-round, the need for an authoritative training guide has never been greater. Training and Conditioning Young Athletes, Second Edition, by world-renowned exercise scientist Tudor O. Bompa and his colleague Sorin O. Sarandan, addresses that need. It provides the blueprint for safely training young athletes to improve performance without hindering overall development and growth.